Application of whole exome sequencing in the diagnosis of muscular disorders: a study of Taiwanese pediatric patients - Lee, Chung-Lin; Chuang, Chih-Kuang; Chiu, Huei-Ching; Chang, Ya-Hui; Tu, Yuan-Rong; Lo, Yun-Ting; Lin, Hsiang-Yu; Lin, Shuan-Pei (Frontiers in Genetics, 2024)
Background: Muscular dystrophies and congenital myopathies encompass various inherited muscular disorders that present diagnostic challenges due to clinical complexity and genetic heterogeneity.Methods: This study aimed to investigate the use of whole exome sequencing (WES) in diagnosing muscular disorders in pediatric patients in Taiwan. Out of 161 pediatric patients suspected to have genetic/inherited myopathies, 115 received a molecular diagnosis through conventional tests, single gene testing, and gene panels. The remaining 46 patients were divided into three groups: Group 1 (multiplex ligationdependent probe amplification-negative Duchenne muscular dystrophy) with three patients (6.5%), Group 2 (various forms of muscular dystrophies) with 21 patients (45.7%), and Group 3 (congenital myopathies) with 22 patients (47.8%).Results: WES analysis of these groups found pathogenic variants in 100.0% (3/3), 57.1% (12/21), and 68.2% (15/22) of patients in Groups 1 to 3, respectively. WES had a diagnostic yield of 65.2% (30 patients out of 46), detecting 30 pathogenic or potentially pathogenic variants across 28 genes.WES enables the diagnosis of rare diseases with symptoms and characteristics similar to congenital myopathy and muscular dystrophy, such as muscle weakness. Consequently, this approach facilitates targeted therapy implementation and appropriate genetic counseling.